Integrated control of Fusarium wilt in banana by Bacillus velezensis EB1 and potassium sorbate - Siwen Liu; Wenlong Yang; Xiaofang Yang; Ronggao Gong; Dandan Xiang; Chunyu Li (BMC Microbiology)
Abstract Fusarium wilt of banana, caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), is a widely distributed soilborne disease that poses a serious threat to banana production. Many control measures have been implemented but have not been effective. Here, we evaluated a combined strategy for Fusarium wilt control that involves a biological agent (Bacillus velezensis strain EB1) and a bioactive compound (potassium sorbate). Our results showed that potassium sorbate inhibited Foc TR4 in a dose-dependent manner. Potassium sorbate did not limit the growth of EB1 in vitro; instead, it promoted the growth and antagonistic ability of EB1 by upregulating the expression of antagonism-related genes. In greenhouse experiments, the combined application of EB1 and potassium sorbate significantly reduced the disease index of Fusarium wilt by suppressing fungal growth in the roots and promoting plant growth. Overall, our results demonstrated that potassium sorbate and B. velezensis EB1 can be used together for the sustainable management of banana Fusarium wilt.